IMPLEMENTASI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN OLEH PLTU PUNAGAYA STUDI KASUS (DI KABUPATEN JENEPONTO) - Ruslan Wahyono, (2021)
Based on Law Number 32 of 2009 Article 68 paragraph 2 that every person conducting a business and / or activity is obliged to maintain the sustainability of environmental functions. In the PLTU Punagaya, there is an allocation of funds for CSR activities in the form of saving the environment by 30%. However, it is suspected that this is still not optimal in reducing the impact on the surrounding community. Efforts to Improve the Community's Economy through Corporate Social Responsibility carried out by PLTU Punagaya are realized in programs in the socio-economic field, including providing food assistance for residents around PLTU, provision of clean water for residents during the dry season, utilization of local labor during the construction period and operations for improving the community's economy, and assistance for youth organizations and emergency response activities in the form of utilizing firefighters for fires. This program is very helpful for the community and village government of Punagaya. However, the community really hopes that the assistance program from the company is in accordance with the problems and needs of the community.